Inherent and Stress-Induced Responses of Fine Root Morphology and Anatomy in Commercial Grapevine Rootstocks with Contrasting Drought Resistance - Idan Reingwirtz; Jake Uretsky; Italo F. Cuneo; Thorsten Knipfer; Clarissa Reyes; M. Andrew Walker; Andrew J. McElrone (Plants, 2021)
Some grapevine rootstocks perform better than others during and after drought events, yet it is not clear how inherent and stress-induced differences in root morphology and anatomy along the length of fine roots are involved in these responses. Using a variety of growing conditions and plant materials, we observed significant differences in root diameter, specific root length (SRL) and root diameter distribution between two commonly used commercial grapevine rootstocks: Richter 110 (110R; drought resistant) and Millardet et de Grasset 101-14 (101-14Mgt; drought sensitive). The 110R consistently showed greater root diameters with smaller SRL and proportion of root length comprised of fine lateral roots. The 110R also exhibited significantly greater distance from tip to nearest lateral, longer white root length, and larger proportion of root length that is white under drought stress. Mapping of fine root cortical lacunae showed similar patterns between the rootstocks; mechanical failure of cortical cells was common in the maturation zone, limited near the root tip, and increased with drought stress for both genotypes; however, lacuna formed under wetter soil conditions in 110R. Results suggest that drought resistance in grapevine rootstocks is associated with thick, limitedly branched roots with a larger proportion of white-functional roots that tend to form lacuna under more mild water deficit, all of which likely favor continued resource acquisition at depth.